2015
DOI: 10.1007/s00167-015-3745-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and muscle activities of the lower limb during a side-cutting task in subjects with chronic ankle instability

Abstract: 1Purpose: The purpose of the present study was to evaluate lower limb kinematics and 2 muscular activities during walking, side-turning while walking, and side-cutting movement in 3 athletes with chronic ankle instability and compare the results to those of athletes without 4 chronic ankle instability. 5Methods: Lower limb kinematics and muscular activities were evaluated in 10 athletes with 6 chronic ankle instability and 10 healthy control athletes using a three-dimensional motion 7 analysis system and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 30 publications
2
43
1
2
Order By: Relevance
“…A recent study suggested that CAI patients increased activation of plantarflexors to stiffen the ankle joint . Similarly, our results suggested CAI patients attempted to increase ankle joint stability and attenuate ankle load immediately after ground contact by increasing MG EMG activation …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A recent study suggested that CAI patients increased activation of plantarflexors to stiffen the ankle joint . Similarly, our results suggested CAI patients attempted to increase ankle joint stability and attenuate ankle load immediately after ground contact by increasing MG EMG activation …”
Section: Discussionsupporting
confidence: 92%
“…However, most studies have examined movement patterns (eg, kinematics, kinetics, and muscle activation) with simple, easy, and/or uniplanar landing tasks such as a drop landing rather than functional activities such as single‐leg landing including sudden deceleration, rapid changing direction, and acceleration. Furthermore, recent studies revealed that CAI affected not only the ankle but also the knee and hip joint biomechanics and neuromuscular patterns . These results provide evidence that mechanisms of CAI may be multifactorial.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations